PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN PELANGGAN PADA MUTIARA RIAU CARWASH PEKANBARU - IKhsan Muhammad; Alwie Furwanti Alvie; Rahayu Danar Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of Service Quality and Store Atmosphere on Purchasing Decisions and Customer Satisfaction at Mutiara Riau Carwash Pekanbaru. Collecting data in this study using a questionnaire survey. The questionnaire was distributed to 100 people who used the services of Riau Mutiara Carwash Pekanbaru. The questionnaire given a number of 100 questionnaires can be used and can be processed as a whole. The data collected is processed using Path Analysis to test the effect of Service Quality and Store Atmosphere on Purchasing Decisions followed by Customer Satisfaction, then testing is conducted to determine the direct and indirect effect of the intervening variables, namely Service Quality and Store Atmosphere on Customer Satisfaction through Decisions. Purchase. The results showed the influence of significant intervening variables from Purchasing Decisions which can increase the value of both Service Quality and Store Atmosphere on customer satisfaction.Keywords: Customer Satisfaction, Purchase Decision, Store Atmosphere, Service Quality